Corporate social responsibility in Nigeria and rural youths in sustainable traditional industries livelihood in oil producing communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
Since the first oil well was drilled in Nigeria, traditional economies have suffered neglect, and rural youths do not see a future for themselves in traditional industries livelihood (TIL). We examine the impact of corporate social responsibility (CSR) of multinational oil companies (MOCs) on youths' participation in TIL. A total of 1200 youths were sampled across the rural Niger Delta. Results from the use of a logit model indicate a significant relationship between CSR and TIL. The findings suggest increased general memorandum of understanding (GMoU) interventions in canoe-carving, pottery-making, cloth-weaving, mat-making, and basket-weaving to revive the traditional economic activities in Nigeria.
Keywords: J43; O40; O55; Q10; 330; corporate social responsibility; multinational oil companies; rural youths; traditionalindustries livelihood; logit model; Nigeria